Pengaruh Jumlah Penduduk, Retribusi Daerah dan Pengeluaran Pemerintah Terhadap Pendapatan Asli Daerah Di Kabupaten Tabanan - Dr. I Nyoman Widya Astawa, S.E,. M.M.; Ni Putu Sudarsani; I. K. Djayastra; I. G. L. Putu Tantra (Universitas Tabanan, 2026)
This study analyzes the influence of population, regional levies, and government spending on Tabanan Regency's Locally Generated Revenue (PAD). Using a quantitative approach, the results show that all three variables simultaneously and partially have a positive and significant effect on PAD. By integrating inclusive economic theory with the strategic role of village governance, this study confirms that optimizing PAD is not merely an administrative matter but rather an instrument for achieving equitable growth. Policy recommendations focus on digitizing levies and strengthening local human resource capacity to address post-pandemic economic dynamics in Bali.